Prevalence of Diarrheagenic E. Coli Among Hospitalized Children in a Clinical Centre - Velev V. (Sciendo, 2021)
Introduction. Escherichia coli is a common cause of acute diarrhea mainly in young children and, less frequently, in elderly or immunosuppressed patients. Many types of E. coli are part of the normal enteric flora, but can cause urinary tract or nervous system infections.